The Effect of Reward, Punishment, Interpersonal Communication and Discipline: Economic Course for Social Students Context - Destri Yaldi; Jumerli Ariati (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
The purpose of this study was to determine the effect of Reward, Punishment, Interpersonal Communication and discipline to social student achievement in economic subject at senior high school Rumbai Pekanbaru. The population in this study as many as 744 students. The sampling technique used was Random Sampling thus obtained a sample of 261 student. The research instrument used in the form of a questionnaire. Analysis of the data in this study using Path Aalysis using program SPSS 16.00 for windows. The results of this study show reward significant and positive impact on the discipline, punishment significant and positive impact on the discipline, interpersonal communication significant and positive impact on the discipline, reward significant and positive impact on the student achievement, punishment significant and positive impact on the student achievement, interpersonal communication significant and positive impact on the student achievement, and discipline significant and positive impact on the student achievement.